LB

A = 2 mũ 2017 + 2 / 2 mũ 2017 +3 và B = 2 mũ 2017 + 1 / 2 mũ 2017 + 2

     so sánh

KN
6 tháng 4 2019 lúc 9:31

Ta có: \(A=\frac{2^{2017}+2}{2^{2017}+3}=1-\frac{1}{2^{2017}+3}\)

        \(B=\frac{2^{2017}+1}{2^{2017}+2}=1-\frac{1}{2^{2017}+2}\)

Vì \(\frac{1}{2^{2017}+3}< \frac{1}{2^{2017}+2}\) nên \(1-\frac{1}{2^{2017}+3}>1-\frac{1}{2^{2017}+2}\)

hay A > B

Bình luận (0)
HM
6 tháng 4 2019 lúc 9:31

A>B bạn nhé

Bình luận (0)

Các câu hỏi tương tự
LM
Xem chi tiết
NM
Xem chi tiết
ND
Xem chi tiết
H24
Xem chi tiết
LP
Xem chi tiết
KA
Xem chi tiết
HN
Xem chi tiết
LV
Xem chi tiết
LM
Xem chi tiết